Does defence expenditure crowd out human capital expenditure? An empirical investigation in South Asia - Jesmy, Abdul Rasheed Sithy (Science and Engineering Research Support Society, 2019)
Military expenditure and human capital expenditure are important components of central government expenditure. It has been accepted that high and increasing military expenditure may crowd out resources from human development expenditure, as the sources of government revenue are limited. The purpose of this study is to examine the relationship between military expenditure and, education and health expenditure in conflict affected five countries in South Asia, namely, Bangladesh, India, Nepal, Pakistan and Sri Lanka from the period 1980 to 2014, by applying the ARDL bounds test approach to cointegration and VECM Granger causality method. The finding of this study shows a significant negative effect of military expenditure on both health and education expenditure in several countries in South Asia. Moreover, it also provides an evidence for Granger causality in the long-run and in the short-run in most of the countries in South Asia. In addition, the findings of this study serve as a guide to the government and the policy-makers should take rigorous steps to minimize military expenditure through preventing conflict and enhancing good governance, which eventually enhance investment in human development